2017
DOI: 10.1039/c6sc03085h
|View full text |Cite
|
Sign up to set email alerts
|

Pickering emulsions stabilized by coloured organic pigment particles

Abstract: Pickering emulsions stabilised by coloured organic pigment particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…18 The emulsion type is primarily determined by the particle wettability at the oil-water interface, although the relative volume fraction of the oil phase can also play a role. 11,[19][20][21] In recent years, there has been growing interest in Pickering nanoemulsions, which comprise droplets of less than approximately 200 nm in diameter. [22][23][24][25][26][27][28][29][30] In contrast to conventional macroemulsions, nanoemulsions are much less prone to gravitational creaming or sedimentation.…”
Section: Commonmentioning
confidence: 99%
“…18 The emulsion type is primarily determined by the particle wettability at the oil-water interface, although the relative volume fraction of the oil phase can also play a role. 11,[19][20][21] In recent years, there has been growing interest in Pickering nanoemulsions, which comprise droplets of less than approximately 200 nm in diameter. [22][23][24][25][26][27][28][29][30] In contrast to conventional macroemulsions, nanoemulsions are much less prone to gravitational creaming or sedimentation.…”
Section: Commonmentioning
confidence: 99%
“…S10A, † successful emulsification was only achieved at extremely high concentrations of SiO 2 particles. In fact, at concentrations lower than 11.2% wt complete destabilization was observed within minutes, as evidenced by the amount of oil resolved (fast creaming of emulsions releases a fraction of pure oil) 34 which is 100% (Fig. S10B † ).…”
Section: Resultsmentioning
confidence: 98%
“…Recently, using the powdered particle method, we have shown the possibility of forming both w/o and o/w emulsions using coloured organic pigment particles as sole emulsifier and we observed that the colour of the emulsions was similar to that of the pigment used. 51 We presented evidence for the link between the tendency of an emulsion to phase invert catastrophically and the surface energy of the pigment for a range of seven pigments. In this work, we show that both stable water-in-heptane and heptane-in-water emulsions can be produced using a mixture of coloured organic pigment particles of different hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%